2005
DOI: 10.1095/biolreprod.104.034736
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Sensitivity of the Bovine Corpus Luteum to Prostaglandin F2α (PGF2α) and Endothelin-1 (ET-1): Is ET-1 a Mediator of the Luteolytic Actions of PGF2α or a Tonic Inhibitor of Progesterone Secretion?1

Abstract: We examined the responsiveness of large luteal cells (LLC), small luteal cells (SLC), and endothelial cells of the Day 4 and Day 10 bovine corpus luteum (CL) to prostaglandin (PG) F2alpha and endothelin (ET)-1. Using a single-cell approach, we tested the ability of each agonist to increase the cytoplasmic concentration of calcium ions ([Ca2+]i) as function of luteal development. All tested concentrations of agonists significantly (P = 0.05) increased [Ca2+]i in all cell populations isolated from Day 4 and Day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 38 publications
13
66
1
Order By: Relevance
“…We showed that TNFα increased secretion of PGF2α and ET-1 by LECs in vitro [24]. In fact, several regulatory factors, including cytokines and angiogenic factors, have been shown to regulate not only vascular function (blood flow) but also progesterone production in LSCs [25][26][27][28]. These findings, together with the positive factor VIII staining and the expression of CD-31 mRNA, confirm that the isolated cells consisted mostly of LECs.…”
Section: Discussionsupporting
confidence: 60%
“…We showed that TNFα increased secretion of PGF2α and ET-1 by LECs in vitro [24]. In fact, several regulatory factors, including cytokines and angiogenic factors, have been shown to regulate not only vascular function (blood flow) but also progesterone production in LSCs [25][26][27][28]. These findings, together with the positive factor VIII staining and the expression of CD-31 mRNA, confirm that the isolated cells consisted mostly of LECs.…”
Section: Discussionsupporting
confidence: 60%
“…Throughout the literature lectin binding is recognized as an indication of carbohydrate expression on endothelial cells and as an endothelial cell marker. Lectin binding has been used extensively to isolate microvascular endothelial cells from CL via magnetic bead separation [18][19][20][21][22]. However, the binding properties of lectins, especially BS-1, are also known to be species-, age-, organ-, and vascular bed-specific [23].…”
Section: Discussionmentioning
confidence: 99%
“…One ml of the cell suspension was placed into five 12 × 75 mm polystyrene round bottom test tubes and centrifuged at 250 × g for 10 min. Cell pellets were resuspended and incubated with 100 μl PBS (control) or FITClabeled Bandeiraea simplicifolia (BS-1) and Concanavalin A (ConA) at a concentration of 2.5 μg/ml for 1 h at 4 C. The lectins BS-1 and ConA have been used routinely to isolate endothelial cells and to assess their functional characteristics within the CL [18][19][20][21][22][23], including at least one study in which lectin binding was compared between luteal microvascular endothelial cells of the estrous cycle and pregnancy [24]. Additional controls included samples containing the competing sugar to BS-1 and ConA (200 mM α-D-galactose and α-D-glucose, respectively) [24].…”
Section: Lectin Binding Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The luteal cell culture procedure was modified from previously published protocols [14,15] as follows. The CL tissue utilized for cell dispersion was sliced with a microtome blade, and the slices were diced with a scalpel into ;1-mm pieces, which were transferred to 50-ml tubes, washed 4 times with HBSS, and shaken (200 rpm for 15 min) in a water bath (378C).…”
Section: Isolation and Culture Of Luteal Cellsmentioning
confidence: 99%